Implementasi Program Keagamaan dalam Internalisasi Nilai-Nilai Religius Siswa di SD Negeri 1 Dukuhagung Tikung Lamongan - Muhamad Anwar; M. Yunus (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2023)
This study aims to examine the implementation of religious programs in the internalization of students' religious values at SD Negeri 1 Dukuhagung Tikung Lamongan. This research uses a qualitative approach with descriptive methods. Research subjects include school principals, teachers, and students. Primary data was obtained through interviews and observations, while secondary data was obtained from school documents and relevant literature. Data collection techniques used are observation, interviews, and documentation. Data analysis was performed using descriptive analysis using words and sentences to explain and interpret data facts. Checking the validity of the data is done through triangulation, namely by comparing data from different sources. The results showed that the implementation of the religious program at SD Negeri 1 Dukuhagung Tikung Lamongan was quite good. Religious program planning is carried out properly through daily, monthly and yearly activities. The implementation of the religious program is carried out by the principal, teachers and school committee with the support of the students' parents. The religious program includes religious learning, worship activities, and religious extracurricular activities. Evaluation of religious program activities is also carried out regularly and has a positive impact on the formation of students' religious character. However, there are several obstacles in the implementation of religious programs, such as limited time, lack of resources, and parents' lack of understanding of the importance of religious education. Nonetheless, support from school principals, teachers, and school committees is essential in overcoming these barriers. This research contributes to thinking and understanding about the implementation of religious programs in the internalization of values.